Breeding Strategies of the Northern Bobwhite in Marginal Habitat - Willie J. Suchy; Ronald J. Munkel (National Quail Symposium Proceedings, 2017)
We studied nesting behavior of radio-tagged northern bobwhite (Colinus virginianus) in south-central Iowa from 1984 to 1988. Female bobwhite incubated 78% of81 clutches where incubation was observed and males incubated 22%. On only 1 occasion were both a male and female observed to incubate the same clutch. Incubation was initiated on 73% of the nests by females before 1 July, while incubation was initiated on 56% of the clutches by males after 1 July. Males hatched 16% of all clutches, first nests by females accounted for 69%, renests for 4%, and second clutches by females that had already hatched 1 clutch for 11 %. Chicks from 3 of the first broods of females that hatched l brood survived for l week and were not accompanied by other adults. These breeding strategies appear to provide bobwhite populations multiple chances at recruitment in variable environments.
Keywords: incubation; nesting; nest success; northern bobwhite